THE ESSENCE OF SMALL BUSINESS AND ITS IMPORTANCE IN THE ECONOMY (SOCIO-ECONOMIC ANALYSIS) - Azimova Shohista; Nilufar Rizayeva (Bright Mind Publishing, 2025)
This article covers the history of the origin of the concept of small business, its essence, its place and necessity in the economy, and its relevance on the basis of socio-economic analysis. The study examines the stages of small business development, its role in increasing economic growth and employment, and measures of state support. On the example of world experience and Uzbekistan, the impact of small business on the economy is analyzed, focusing on its prospects and existing problems. The results of the study serve to promote proposals and recommendations aimed at further development of small businesses.
Keywords: Small business, economy, entrepreneurship, socio-economic analysis, innovation, employment, world economy, economic diversification of economic recovery of technological progress.